KUALITAS PELAYANAN CALON JAMA’AH HAJI DI KEMENTRIAN AGAMA KOTA PALU - Sumalki, Sumalki; Mustainah, Mustainah; Khairil, Muhammad (Katalogis, 2019)
This research aims to find out and explain the quality of service for prosvectipe pilgrims at the ministry of religion in the city of palu. This research is qualitative research. Informants were selected by purposive sampling which consisted collection of employees of the Ministry of Religion in Palu and 8 Hajj Pilgrims. Data collection cwas observation, interview, and documentation. Technique of data analysis was data gathering, data reduction, and data display and verification/drawing conclusion. Thery used was from Parasuraman. The research results show there are two indicators that are adequate and three have not been good. I. the tangible aspect, facilities and infrastructure used in the service of prospective pilgrims are not yet adequate. 2. Reliability, accuracy and suitability of procedures in the service have been assessed both the service shown by the employee is not target and according to the procedure. 3. Responsiveness, the response in service is considered as inadequate in performing service services, the response is slow and there are differences in services shown by employees. 4. Ssurance, guarantees are considered to be good where employees provide guarantees when leaving to the holy land and guarantee the security of prospective pilgrims in the management up to leaving for the holy land. Empathy, caring where employees show a caring attitude towords prospective pilgrims in service so that communication is established.